Interference Alignment for the Uplink Heterogeneous Cellular Networks - Gao Yingyuan; Wang Gang; Cui Siqian (MATEC Web of Conferences, 2016)
Heterogeneous cellular networks, due to its multi-tier topological structure, provide significant improvements in terms of increased data rates and cell coverage. However, there are important intra-tier and inter-tier interference management problem to be solved. In this paper, we model a two-tier uplink heterogeneous network, which include a macrocell and K overlaid femtocells. Meanwhile we constitute a heterogeneous configuration that each femto BS is equipped with two antennas and the macro BS is equipped with A(2 ≤ A ≤ 2K) antennas. We proved that the sum-DoF outer bound of the network is 4K2/4K ‒ A, and the DoF outer bound for the femtocell and macrocell is (2K‒A)/(4K‒A) and A/(4K‒A) respectively. Moreover, we present the achievable scheme, which is based on interference alignment. The simulation results show that the sum rate of the whole HetNet increases as the number of macro BS’s antennas increases.